EXPLORING IRREGULAR VERB ACQUISITION IN INDONESIAN EFL LEARNERS’ SPEAKING THROUGH NARRATIVE AND RECOUNT LESSON: A QUALITATIVE STUDY - Erly Mulfias Yuli; Aizzatul Hijaiyah; Nabila Ramadani; Ghitif Cavan El-Hadya (Premise: Journal of English Education and Applied Linguistics, 2026)
The using of irregular verbs still remains challenges for Indonesian high school students, especially in spontaneous oral communication. Although learners often recognize irregular verb forms in written contexts, they frequently fail to apply them accurately in speaking. This qualitative case study investigates how Indonesian secondary school EFL learners acquire and use irregular verbs in speaking activities, identifies common error patterns, and examines the role of comprehensible input in supporting this acquisition. Data were collected from ten classroom observation videos of narrative and recount text lessons across different Indonesian high schools. The videos were purposively chosen based on the participants who are 10 grade senior high school students that learn narrative and recount text. Furthermore, the videos were transcribed and analyzed using IRF (Initiation–Response–Feedback) classroom discourse analysis and error analysis within an interlanguage framework to find how the students’ repertoire in speaking irregular verbs through narrative and recount text topics. Acquisition was inferred from recurring pattern of students oral production. The findings reveal that students were generally able to convey past events fluently but demonstrated unstable control of irregular verb forms, frequently relying on base forms, overgeneralization, and inconsistent tense marking. Pedagogically, irregular verbs acquisition in speaking requires sustained instructional support alongside meaningful speaking practice. The implication of this study suggests that meaningful speaking activities may not be sufficient to facilitate irregular verbs acquisition. It is important to integrate communicative practice that are complemented by systematic grammatical support and language input. Keywords: irregular verb, interlanguage ,second language acquisition (LS), speaking skill, EFL learners